Stroke in Sickle Cell Disease: Recent Successes - Cunningham, Muriel (MD Conference Express, 2008)
The reported incidence of all types of stroke in childhood is relatively low, with 2.6 occurring per 100,000 white children and 3.1 per 100,000 in black children [Broderick et al. Child Neurol 1993]. However, additional analyses indicate that children with sickle cell disease (SCD) face a huge relative risk of ischemic stroke compared with a healthy population (RR=220) [Earley et al. Neurology 1998]. Chronic blood transfusion therapy has been employed as secondary prevention of stroke in patients with SCD for over 30 years